(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Modern Kazakh society is actively integrating into the global conscience, expanding worldwide socio-economic, political and cultural connections. In connection with this, the question of specialized, particularly legal, translation is of particular importance due to its instrumental role in the establishment of international relations, which hinge on legal organization and professionally trained specialists who are able to, depending on the situation, actively switch from one language to another. The article deals with phrasal verbs, which are actively used within legal literature. These verbal constructions, consisting of a verb and a postposition, are idiomatical lexical units characteristic only of the English language. As a result of the research, the most frequently used phrasal verbs used in legal literature in English were identified. While working with the British National Corpus (BNC) as well as with the Corpus of Contemporary American-English (COCA) it was revealed that the quantity of phrasal verbs used in legal literature in English has been growing steadily. Linguistic particularities, which may complicate the phrasal verb translations from English to Russian, were brought to light based on analysis regarding dictionary definitions and translational equivalents.